ANALISIS PENERAPAN GOOD AGRICULTURAL PRACTICES (GAP) PADA USAHATANI HORTIKULTURA DI DESA AUNUPE KECAMATAN WOLASI KABUPATEN KONAWE SELATAN - Putri, Dessri Natalia; Arimbawa, Putu; Mardin, Mardin (Department of Agricultural Extension, Faculty of Agriculture, Halu Oleo University, 2025)
The objective of this study is to ascertain the extent of implementation of Good Agricultural Practices (GAP) and the factors that influence the implementation of Good Agricultural Practices (GAP) in horticultural farming in Aunupe Village, Wolasi District, South Konawe Regency. The population under study comprised horticultural farmers who were affiliated with farmer groups in Aunupe Village, amounting to a total of eight farmer groups and 134 members. The sample size was determined using the Slovin formula with a margin of error of 10%, resulting in a sample size of 57 farmers. The sampling technique that was employed was proportional random sampling. The present study employs a quantitative research method. The study's primary focus is on the level of implementation of Good Agricultural Practices (GAP) and the factors that influence the implementation of Good Agricultural Practices (GAP). The research data were analyzed using quantitative descriptive statistical methods. Subsequent analysis was executed employing the class interval formula and simple linear regression analysis with the assistance of SPSS version 24 software. The results of the study show that the implementation of Good Agricultural Practices (GAP) in horticultural farming in Aunupe Village, Wolasi District, South Konawe Regency is still moderate, with weaknesses in the aspects of environmental friendliness, consumption safety, and production sustainability. Factors such as age, education, land area, income, and the role of extension workers were found to significantly influence the implementation of Good Agricultural Practices (GAP), while experience had no significant effect. Farming experience, which has been considered important, does not appear to be a dominant factor in the implementation of Good Agricultural Practices. This condition emphasizes the need to increase farmer capacity through education, training, and extension support to accelerate the optimal adoption of Good Agricultural Practices.